Desigualdade de Carleman e Controlabilidade Nula para uma EDP com Coeficientes Complexos - Santos, Maurício Cardoso (2010)
In the present work, we study controllability results for two problems on the theory of the partial differential equations. We use global Carleman inequalities to show the null controllability for the heat equation and for a PDE with complex principal part. We obtain the control of minimal norm solving a dual minimization problem.